WAYS TO INCREASE THE EFFECTIVENESS OF GREEN MARKETING IN THE DEVELOPMENT OF ECO-TOURISM PRACTICE (World Bulletin of Public Health, 2023)
In this article, green marketing in ecotourism refers to the promotion of sustainable tourism methods with minimal environmental impact while providing tourists with an authentic experience that allows them to communicate with nature. The theoretical foundations of the effectiveness of green marketing in the development of ecotourism practice are analyzed
Keywords: Ecotourism; marketing; green marketing